2009
DOI: 10.1183/09031936.00121008
|View full text |Cite
|
Sign up to set email alerts
|

FcϵRI-mediated thymic stromal lymphopoietin production by interleukin-4-primed human mast cells

Abstract: A significant increase of mRNA expression of thymic stromal lymphopoietin (TSLP) has been reported in the bronchial mast cells (MCs) of asthmatic subjects; however, the mechanism underlying the upregulation of TSLP mRNA and protein remains unknown.FceRI-mediated activation of human MCs upregulated TSLP mRNA expression by 5.2¡2.9-fold, while activation of the MCs using lipopolysaccharide and polyriboinosinic:polyribocytidylic acid failed to upregulate TSLP. Stimulation of MCs with interleukin (IL)-4 alone did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 26 publications
2
85
1
2
Order By: Relevance
“…It has been reported that MCs are able to produce all three cytokines, [28][29][30] thus, one possibility is that MCs themselves contribute to the enhanced expression of these factors following Hp infection. However, it is unlikely that MCs-a relatively rare population in the steady-state/ early-infected intestine-produce sufficient quantities of these cytokines alone.…”
Section: How Do Mast Cells Sense Gastrointestinal Helminthmentioning
confidence: 99%
“…It has been reported that MCs are able to produce all three cytokines, [28][29][30] thus, one possibility is that MCs themselves contribute to the enhanced expression of these factors following Hp infection. However, it is unlikely that MCs-a relatively rare population in the steady-state/ early-infected intestine-produce sufficient quantities of these cytokines alone.…”
Section: How Do Mast Cells Sense Gastrointestinal Helminthmentioning
confidence: 99%
“…We do not know whether RabGEF1 has this effect through direct or indirect mechanisms, but it is known that epithelia of the skin, intestine, and respiratory tract are the major sources of TSLP 3 and that production of TSLP in these epithelial cells can be induced by active vitamin D 3 (1a,25-(OH) 2 D 3 ) or its low calcemic analog, 31 proinflammatory cytokines, [32][33][34][35] and various TLR ligands. 33,35 In addition, bone marrow-derived cells, including human mast cells 36 and mouse basophils, 37 also can produce TSLP. While current understanding of the mechanisms regulating TSLP production is rather limited, NF-B-binding sites are present in the promoters of both human and mouse TSLP genes, 35 and there is evidence supporting an involvement of NF-B pathways in the regulation of TSLP production.…”
Section: Discussionmentioning
confidence: 99%
“…В первый раз ТСЛП был об-наружен в культуре тимических клеток, откуда по-лучил свое название. Анализ библиотек кодирую-щих ДНК клеточных линий и первичных культур различных тканей показал, что не только кератино-циты и эпителиальные клетки, но и гладкие мышеч-ные клетки, легочные фибробласты, активирован-ные связыванием IgE тучные клетки, а также акти-вированные дендритные клетки в больших количе-ствах экспрессируют и продуцируют ТСЛП [18][19][20][21][22][23]. Продукция ТСЛП усиливается разными цитокина-ми: ИЛ-4, ИЛ-13, ИЛ-1b, ИЛ-25, ИЛ-33, фактором некроза опухоли альфа (ФНО-α), интерферонами-α и -β и другими [19,20,22].…”
Section: механизмы контроля целостности барьеров организма млекопитающихunclassified